PsycEXTRA Dataset 2014
DOI: 10.1037/e515492014-005
|View full text |Cite
|
Sign up to set email alerts
|

The psychophysiology of mixed emotional states

Abstract: How to conceptualize mixed emotional states is a central issue in the field of affective science. Nondifferentiation, additive, and emergence accounts of mixed emotions make divergent predictions regarding physiological responses in mixed emotions. To test these predictions, 43 women watched film clips that elicited amusement, disgust, or mixed emotions while feeling self-report, facial electromyography, cardiovascular, electrodermal, and respiratory measures were assessed. Simultaneous self-reports of amuseme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 3 publications
2
26
0
Order By: Relevance
“…Consistent with our previous study (Kreibig et al, ), amusement led to decreased cardiac activity, peripheral vasoconstriction, decreased electrodermal activity, and faster and shallower breathing; the current study additionally showed increased vagal reactivity and PVA. Both internal and external replicability analyses identified HR, TPR, FT, SCL, RR, and V i as measures with replicable results, suggesting involvement of cardiovascular, electrodermal, and respiratory systems in amusement.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with our previous study (Kreibig et al, ), amusement led to decreased cardiac activity, peripheral vasoconstriction, decreased electrodermal activity, and faster and shallower breathing; the current study additionally showed increased vagal reactivity and PVA. Both internal and external replicability analyses identified HR, TPR, FT, SCL, RR, and V i as measures with replicable results, suggesting involvement of cardiovascular, electrodermal, and respiratory systems in amusement.…”
Section: Discussionsupporting
confidence: 93%
“…Profile analyses on physiological variables that had a significant univariate omnibus effect in the previous study (Kreibig et al, ) and on those that were significant in both the current and previous study showed significant condition effects for amusing versus disgusting and mixed versus amusing film clips. We again found significant Condition × Variable effects for all three contrasts (Table middle and bottom and Figure b and c).…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Many temperament researchers have focused specifically on young children's parasympathetic nervous system (PNS) functioning. From this work, scientists have been able to identify PNS biomarkers and highlight the important role they play in individuals’ ability to modulate their state, emotions, and arousal in ways that allow them to react in a socially appropriate manner (Kreibig, Samson, & Gross, ; Porges, ).…”
Section: Biopsychosocial Model Of Temperamentmentioning
confidence: 99%